2020
DOI: 10.1111/aec.12920
|View full text |Cite
|
Sign up to set email alerts
|

Trophic structure of frog assemblages in coastal habitats in southern Brazil

Abstract: We evaluated the hypothesis that contrasting environmental conditions in a coastal wetland and nearby sand dunes results in frog assemblages with divergent trophic structures. We predicted that the more productive habitat (wetland) would have higher diversity of primary producers and frogs with larger trophic niches and greater interspecific dietary overlap when compared to the less-productive dune habitat. Stomach content analysis (SCA) and stable isotope analysis (SIA) were used to compare frog trophic ecolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
(128 reference statements)
0
4
0
Order By: Relevance
“…In contrast, intermediate (40–80 mm) and larger (>80 mm) individuals had smaller isotopic niches, which could be associated with a less diverse diet. We proposed two non-mutually exclusive hypotheses that could explain the higher isotopic niche observed in the smaller individuals: (i) only smaller individuals consumed terrestrial preys (insects) that tend to have distinct isotopic composition than marine preys (Garcia et al ., 2019b; Huckembeck et al ., 2020), which may have contributed to increase the size of their isotopic ellipses, and (ii) considering that the isotopic muscle turnover (i.e. the time the tissue takes to reflect a new food source) of marine fishes is approximately three months (Mont'alverne et al ., 2016; Oliveira et al ., 2017), the smaller individuals sampled in the surf zone could be partially reflecting offshore food sources, since they originally migrate (as eggs and larvae) from the deeper coastal zone (40 m) into the surf zone (2 m) in the summer period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, intermediate (40–80 mm) and larger (>80 mm) individuals had smaller isotopic niches, which could be associated with a less diverse diet. We proposed two non-mutually exclusive hypotheses that could explain the higher isotopic niche observed in the smaller individuals: (i) only smaller individuals consumed terrestrial preys (insects) that tend to have distinct isotopic composition than marine preys (Garcia et al ., 2019b; Huckembeck et al ., 2020), which may have contributed to increase the size of their isotopic ellipses, and (ii) considering that the isotopic muscle turnover (i.e. the time the tissue takes to reflect a new food source) of marine fishes is approximately three months (Mont'alverne et al ., 2016; Oliveira et al ., 2017), the smaller individuals sampled in the surf zone could be partially reflecting offshore food sources, since they originally migrate (as eggs and larvae) from the deeper coastal zone (40 m) into the surf zone (2 m) in the summer period.…”
Section: Discussionmentioning
confidence: 99%
“…These comprised (1) hippid crab Emerita brasiliensis, (2) juvenile fishes of the mullet Mugil liza and T. marginatus with TL between 17.0 and 24.5 mm, (3) insects of the orders Hymenoptera, Hemiptera, Coleoptera and Odonata, (4) the polychaeta Spio gaucha and (5) the bivalve Amarilladesma mactroides. These prey species were sampled in the same studied sandy beach where basal sources (POM and SOM) were obtained, with exception of the insects and annelids that were obtained from the literature (Huckembeck et al, 2020 andGarcia et al, 2019b, respectively). These studies were carried out in the same coastline of the present study (29°59 ′ S): the former in a sandy dune adjacent to the marine surf zone (31°08 ′ S) and the latter in a sandy beach (32°17 ′ S), respectively.…”
Section: Field Collections and Sample Processingmentioning
confidence: 99%
“…The composition of communities can be influenced by primary productivity, climate and elevation, among other factors (Davey et al, 2013; Perillo et al, 2021; Siemann, 1998). For example, primary productivity affects the richness of invertebrates, particularly arthropods, such that more productive environments provide a greater variety of prey for secondary consumers (Huckembeck et al, 2020). In addition, arthropod consumer populations can exhibit significant variations in diet in environments with different elevation gradients, as the diversity of arthropods decreases at higher elevations (Galetti et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Water is generally scarce in the Tottori Sand Dunes, and there are a small stream and a small pond surrounded by sand and patchy vegetation. Recently, Huckembeck et al (2020) suggested that frogs that inhabit sand dunes might differ in diet from frogs that inhabit coastal wetlands in Brazil. Frogs do not frequently inhabit beaches or coastal sand dunes, however approximately 100 frogs per year had been detected around the stream and the pond in the Tottori Sand Dunes from 2017 to 2021 (H. Chiba, data not shown).…”
Section: Introductionmentioning
confidence: 99%